REFORMING THE UNITED NATIONS: REALITIES, EXPECTATIONS, AND THE WAY FORWARD - Joy Henri Mangapul (Padjadjaran Journal of International Law, 2019)
AbstractThe United Nations was born as an end-result of the Second World War. Its stated purpose was obvious as enshrined in the Charter of the United Nations (“the Charter”) – to maintain international peace and security. The United Nations, however, both in terms of practicality and the will to do such, had been burdened by several problems surrounding them; the ineffectiveness of several bodies such as the Trusteeship Council, the Economic and Social Council (“ECOSOC”), etc.; the overwhelming power of the veto rights vested towards the five permanent members of the United Nations Security Council ("the UNSC"); the strength of certain resolutions towards the international community, to name a few. Though one of the keys to reform the United Nations is by amending the Charter itself, the current development on the issue seems – and continues to seem – moot. Thus, the will to reform has to be from the United Nations itself, since the organization is expected to develop with time and the community, instead of being extremely rigid, dead-locked international organization. Keywords: Charter of the United Nations, organization, reform, resolution, United Nations. AbstrakPerserikatan Bangsa-Bangsa lahir sebagai hasil akhir, atau akibat, dari Perang Dunia Kedua. Tujuan tersurat PBB adalah telah jelas sebagaimana yang tercantum dalam Piagam Perserikatan Bangsa-Bangsa – menjaga perdamaian dan keamanan internasional. Sekalipun demikian, PBB baik secara praktis maupun melihat niat, nyatanya menemui rintangan dan permasalahan yang mengelilinginya seperti tidak efisiennya beberapa badan seperti Badan Perwalian (Trusteeship Council), Badan Ekonomi dan Sosial (ECOSOC), dan sebagainya; kekuatan berlebihan berkenaan hak veto bagi lima negara anggota permanen Dewan Keamanan PBB; kekuatan resolusi-resolusi tertentu terhadap komunitas dunia, dan masih banyak lagi. Sekalipun salah satu kunci reformasi PBB ialah dengan mengamandemen piagam PBB itu sendiri, perkembangan yang terjadi membuat hal tersebut menjadi angan semu semata. Tekad mereformasi PBB sudah sewajarnya berasal dari PBB sendiri. Oleh karenanya, PBB diharapkan untuk berkembang seiring waktu juga dengan komunitas global, bukan menjadi organisasi yang kaku dan terkungkung. Kata Kunci: Organisasi, reformasi, resolusi, Perserikatan Bangsa- Bangsa, Piagam PBB